Ridiculing Capitalism in Bertold Brecht’s Caucasian Chalk Circle - Darman Sitepu; M. Amrin Siregar (Proceedings of AICS - Social Sciences, 2017)
Brecht’s Caucasian Chalk Circleis pervasive with ridicule. The ridicule is conveyed subtly and interestingly that capitalists do not realize that they are the objects of ridicule. The dispute between two groups of peasants is settled ridiculously. The original owners are disowned because the other can make a better use of the land that may lead to prosperity for all. In the physical contest of theCaucasian Chalk Circle, the judge also disowns the original mother and submits the baby to the foster mother. In the next other cases, the judge coins the verdicts which are contradictory to capitalist legal system. In the case of the doctor and his patient, the case of old woman and famers, and the case of stableman and inn keeper, the judge sides the poor or down-trodden people. In court proceedings, Azdak, ridiculous judge, makes ridiculous verdict that evokes our laughter. The humor in court is so interesting that the capitalists also laugh without realizing that they are laughing at themselves. Keywords:ridiculing, communist, communal interest, religion, legal system.